Cartografia da constituição e do funcionamento discursivo da ciberautoridade em grupo de Facebook - Silva, Ana Paula Ramao da (2023)
The intersection between the virtual and the physical has exposed the inadequacy of binary logic and the arborescent image for the problematization of the world. This has enabled reconfigurations and re-significations of authority discourses in cyberculture. Reflections on this fact led us to the following question: what movements constitute and put into operation discourses of authority in cyberculture? As a thesis, we argue that cyberculture fosters the production, circulation, and reception of natively digital discourses axiologically in tension with the discourses of institutional authorities, what we have called cyber-authority. This is an indication of consistent changes in everyday ideology. This research aims to cartograph cyber-authority in utterances from the Facebook group "Voluntary Death" between 2012/2014 and 2016/2019. To this end, we draw on theoretical rhizomes between the production of Bakhtin's Circle and Deleuze and Guattari's Philosophy of Difference. This is field research, of qualitative nature and interpretative nature, of cartographic nature, situated in Applied Linguistics (AL), with punctuations of the methodological approaches of the Dialogical Discourse Analysis (DDA) and the Actor-Network Theory (TAR). The analyses show that cyber-authority emerges from the agency in which the human and the non-human elements are imbricated under the chronotope virtuality. Thus, cyber-authority, as a discursive reality of cyberculture, in the Facebook group "Voluntary Death" between 2012/2014 and 2016/2019, can both stimulate escape lines and molar lines. It is constituted by a rhizomatic discursive mesh woven by assimilation that questions and invalidates institutional discourses as well as resignifies and appropriates them. With this, it sustains de(re)territorializations that problematize society's territorializing and regulating discourses, coercive of free will. To function, it intersperses genres from other fields of human activity (report, opinion article, death note, personal letter, advice letter, classified, review) in the agency to free will, to sharing facts of intimate life and technodiscourse. The cartography performed shows that cyber-authority mobilizes discursive flows, like the war machine proposed by Deleuze and Guattari, that disassembles striated spaces and prepares smooth spaces